Implementasi Model Pembelajaran Outdoor dalam Meningkatkan Minat Belajar Anak - Danang Prastyo; Selfi Lailiyatul Iftitah; Trisa Kumalasari; Alfarobi Ahmad Sulaiman; Lailatul Firdausi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2026)
Children’s interest in learning is a key factor influencing academic achievement. One approach that can be used to enhance it is outdoor learning, which emphasizes hands-on and contextual learning experiences. This study aims to describe the implementation of an outdoor learning model in enhancing children’s interest in learning. The research method employed a descriptive qualitative approach, with data collected through observation and in-depth interviews. The study involved six informants, including the principal and teachers at Al-Amin Kadur Kindergarten in Pamekasan. Data analysis utilized the Miles and Huberman model, proceeding through the stages of data reduction, data presentation, and drawing conclusions. Research findings indicate that outdoor learning, conducted outside the formal classroom setting and utilizing the surrounding environment as a learning resource, encourages children’s active engagement through direct interaction with real-world objects, enhances their focus, and broadens their participation in the learning process. Supporting factors include the availability of adequate learning facilities and resources, the use of the school’s surrounding environment as a learning resource, and warm emotional bonds between teachers and students. In contrast, inhibiting factors include students’ lack of concentration when outside the classroom, limited learning time, and external distractions such as vehicle traffic around the school. This study contributes to the development of environment-based learning strategies as an alternative to contextual approaches in early childhood education